2016
DOI: 10.1002/tox.22305
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR induces a wide variety of biochemical changes in the A549 human non-small cell lung cancer cell line: Roles for protein phosphatase 2A and its substrates

Abstract: Our previous studies have described the toxic effects of microcystin-LR (MC-LR) in various normal cell lines and human hepatoma SMMC-7721 cells, but the specific effects of MC-LR in other types of cancer cells with respect to protein phosphatase 2A (PP2A) have not been fully elaborated. A549 human lung adenocarcinoma cells have been identified to express organic anion-transporting polypeptides (OATP) involved in cellular uptake of MC-LR, and thus probably make an appropriate in vitro model to assess MC-LR's cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Although these results suggest uptake of MC-LR and its interaction with cellular proteins, the viability assays did not reveal any major effects of MC-LR in both HBE1 and 16HBE14o-cells. The results of our study are mostly consistent with findings of Wang et al [25], who found no significant effect of 10 µM MC-LR on viability in A549 human non-small lung cancer cells following 24-h exposure. On the contrary, Li et al [29] found that 10 µM MC-LR significantly reduced (EC50) cell survival in HBE cells after 24 h, and concentrations ≥50 nM were cytotoxic to immortalized murine alveolar type II cell line [45].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although these results suggest uptake of MC-LR and its interaction with cellular proteins, the viability assays did not reveal any major effects of MC-LR in both HBE1 and 16HBE14o-cells. The results of our study are mostly consistent with findings of Wang et al [25], who found no significant effect of 10 µM MC-LR on viability in A549 human non-small lung cancer cells following 24-h exposure. On the contrary, Li et al [29] found that 10 µM MC-LR significantly reduced (EC50) cell survival in HBE cells after 24 h, and concentrations ≥50 nM were cytotoxic to immortalized murine alveolar type II cell line [45].…”
Section: Discussionsupporting
confidence: 93%
“…To evaluate possible effects of a very abundant cyanotoxin MC-LR in the human respiratory system, we used two immortalized, non-cancerous, respiratory-relevant human bronchial epithelial cell lines. The concentrations of MC-LR in our experiments were chosen based on previous studies with human bronchial or alveolar cells [25,29], where MC-LR at relatively high concentrations (30-40 µM) nearly completely inhibited cell viability after 24-h exposure, while 1-20 µM significantly reduced cell viability to 90%-35% of the control [29]. Thus, in our prolonged exposure (48-96 h) experiments, we decided to test a concentration range of 1-20 µM MC-LR, while using 1 µM MC-LR to assess the effects of a toxicologically more feasible concentration on a sub-cellular level for mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to CTD and NCTD, CAC has been recognized as a protein phosphatase 2A (PP2A) inhibitor . Interestingly, PP2A is thought to be a cancer suppressor, as inhibition of PP2A can induce phosphorylation and activation of substrate kinases, most of which can further accelerate growth . JNK and p38 MAPK have been reported to be the direct substrates of PP2A .…”
Section: Discussionmentioning
confidence: 99%